Evaluasi Dan Perbaikan Proses Penjemuran Kain Batik Cabut Pada Industri Batik Gress Tenan (Studi Kasus: Proses Grounding) - Marzuki, Ahmad Ali; , Etika Muslimah, S.T., M.M., M.T; , Ida Nursanti, ST., M.Eng.Sc (2015)
Gress Tenan Batik industry produces several types of batik is batik unplug one of them. Unplug batik batik fabric is given a basic color or can be called by the grounding. Fabrics that have gone through the process of grounding will then be dried in the sun. Wet cloth will be brought to a grounding outcome drying to perform the next process is drying the fabric. Preparation (set up) is done by pulling at the fabric of the floor and fixes the fabric to pin multiple times at a certain distance. From this background, this study aims to evaluate the work set up drying on the grounding to reduce the risk of injury or operator fatigue and how to reduce product defects that occur. The next goal is to repair the fabric drying remove the grounding process. The method used to meet the goals of this research is the Nordic Body Map method used to determine the complaints experienced by the operator by means of interviewing the operator about any posture that have complaints. Making the design tools is also proposed in an effort to make improvements to the drying fabric grounding process results. In order to know the criteria for tools that can meet the needs of the operator by using Quality Function Deployment (QFD) / House of Quality (HOQ) and anthropometric data. The tools are made to reduce the activity of the operator bent when performing the drying process. These do not need to lift the fabric from the grounding process to the drying process. The proposed tool also reduces the fabric touching the floor, so that the fabric does not become dirty, which is one form of disability. Needle pin that is used to associate the fabric when drying was changed to clamp, so that the fabric is not perforated or torn. Ropes used to tie the fabric is made of the same length and the distance between the rope and the rope the other one was also made within 1 meter so that the fabric does not sag that would make the fabric be spotted. Keywords: Nordic Body Map, Qualiy Function Deployment (QFD), House of Quality (HOQ), anthropometry, Tools.